A cross-industry analysis on labor productivity comparing productivity differentials between agricultural and non-agricultural occupational divisions in the Philippines - De la Cruz, Krista Dominique P. (School of Economics, University of the Philippines Diliman, 2018)
Despite the overall upward trend of economic growth in the Philippines, not all industries are as equally productive. Among them is the agricultural industry which experienced decline in Gross Domestic Product and mobility in its workforce these past few years. The implications of these problems affect not only the individual players of this industry, but even the overall condition of agricultural sector in our country. This paper aims to fill the gap by addressing occupational workforce attributions that may affect the productivity of an industry and its effect to the productivity_wage gap relationship. This was achieved by using multiple regression analysis and the Juhn Murphy Pierce Decomposition in measuring and decomposing the productivity differentials over a given time period, 2012 to 2016. The results suggest that the consistent output differential between the agricultural and non_agricultural sector are translated through their productivity gaps, particularly for the services and manufacturing sub industries. Productivity differentials for non_agricultural sectors are percentage points more significant as compared to the agricultural sector. There also remains a consistent trend for significant occupational characteristics across highly productive industries. Lastly, the relative wages tend to be lower than the labor productivity of the agricultural sector as compared to other industries thus challenging Classical Labor Economic Theory. In short, the lack of proper capital investment, workforce characteristics and proper wage in the agricultural sector can pose a threat to its productivity.